Suppression of AC overvoltage at sending end under DC transmission system fault based on controllable energy dissipation - Yongrui HUANG; Kun HAN; Qiuling HU; Wenbo ZHANG; Hongtao YUAN; Zhuke SHAO (电力工程技术)
In the conventional high voltage direct current transmission system with large-scale new energy access, when commutation failure or DC blocking occurs at the receiving end, the reactive power surplus at the sending converter station may cause overvoltage in the AC system. In order to suppress the overvoltage at the sending end, an overvoltage suppression device is proposed based on the principle of controllable energy dissipation. Firstly, the overvoltage mechanism in weak AC system under the fault of DC system is analyzed, and the topology and working principle of the controllable energy dissipation device are proposed. Secondly, the suppression effect and electrical stress of the controllable dissipation device on AC system overvoltage under typical fault conditions is simulated and studied. Then, the design of the controllable dissipation device is carried out, focusing on the potential distribution of the arrester and the the static and dynamic characteristics of electromagnetic repulsion of the trigger switch under different coil turns, the entry and exit control strategy of the dissipation device is proposed. Finally, the experimental verification of the energy dissipation device prototype is carried out, proving the correctness of the design. The energy dissipation device developed is successfully applied to the ±800 kV Lu-Gu high voltage direct current transmission project, and the operation results show that the controllable energy dissipation device can effectively suppress of AC overvoltage.